I love dinosaurs [videorecording (DVD)] - Bredar, John B.; Schiliro, Jody; Sereno, Paul C. (National Geographic Video, 2011)
National Geographic puts together two dinosaur stories with a question and answer period with children before each segment. See a new never-before-seen dinosaur, the Jobaria. Meet Sue the T.rex, she's 67 million years old and is the world's largest and most complete T.rex ever found.